Apolipoprotein E (APOE) genotype regulates body weight and fatty acid utilization—Studies in gene‐targeted replacement mice. Issue 2 (12th December 2014) - Huebbe, Patricia; Dose, Janina; Schloesser, Anke; Campbell, Graeme; Glüer, Claus‐Christian; Gupta, Yask; Ibrahim, Saleh; Minihane, Anne‐Marie; Baines, John F.; Nebel, Almut; Rimbach, Gerald
<x xml:space="preserve">Abstract</x> Scope Of the three human apolipoprotein E (APOE) alleles, the ε3 allele is most common, which may be a result of adaptive evolution. In this study, we investigated whether the APOE genotype affects body weight and energy metabolism through regulation of fatty acid utilization. Methods and results Targeted replacement mice expressing the human APOE3 were significantly heavier on low‐ and high‐fat diets compared to APOE4 mice. Particularly on high‐fat feeding, food intake and dietary energy yields as well as fat mass were increased in APOE3 mice. Fatty acid mobilization determined as activation of adipose tissue lipase and fasting plasma nonesterified fatty acid levels were significantly lower in APOE3 than APOE4 mice. APOE4 mice, in contrast, exhibited higher expression of proteins involved in fatty acid oxidation in skeletal muscle. Conclusion Our data suggest that APOE3 is associated with the potential to more efficiently harvest dietary energy and to deposit fat in adipose tissue, while APOE4 carriers tend to increase fatty acid mobilization and utilization as fuel substrates especially under high‐fat intake. The different handling of dietary energy may have contributed to the evolution and worldwide distribution of the ε3 allele.